Solution‐Processable Thermally Crosslinked Organic Radical Polymer Battery Cathodes. Issue 9 (5th March 2020) - Wang, Shaoyang; Park, Albert Min Gyu; Flouda, Paraskevi; Easley, Alexandra D.; Li, Fei; Ma, Ting; Fuchs, Gregory D.; Lutkenhaus, Jodie L.
Abstract: Organic radical polymers are promising cathode materials for next‐generation batteries because of their rapid charge transfer and high cycling stability. However, these organic polymer electrodes gradually dissolve in the electrolyte, resulting in capacity fade. Several crosslinking methods have been developed to improve the performance of these electrodes, but they are either not compatible with carbon additives or compromise the solution processability of the electrodes. A one‐step post‐synthetic, carbon‐compatible crosslinking method was developed to effectively crosslink an organic polymer electrode and allow for easy solution processing. The highest electrode capacity of 104 mAh g −1 (vs. a theoretical capacity of 111 mAh g −1 ) is achieved by introducing 1 mol % of the crosslinker, whereas the highest capacity retention (99.6 %) is obtained with 3 mol % crosslinker. In addition, mass transfer was observed in situ by using electrochemical quartz crystal microbalance with dissipation monitoring. These results may guide future electrode design toward fast‐charging and high‐capacity organic electrodes. Abstract : Get radical : A one‐step post‐synthetic crosslinking method that is compatible with solution processing is developed to improve the performance of organic polymer electrodes. The highest electrode capacity of 104 mAh g −1 (vs. a theoretical capacity of 111 mAh g −1 ) is achieved by introducing 1 mol % crosslinker, whereas the highest capacity retention (99.6 %) is obtained with 3 mol % crosslinker.